1991
DOI: 10.1080/01431169108955256
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rice yield using IRS-1A digital data in coastal tract of Orissa

Abstract: An attempt to derive a relation between spectral data of rice canopies and their grain yield has been made in the Cuttack and Puri districts of Orissa for Kharifrice using Landsat MSS digital data of three years (1984)(1985)(1986). Necessary sensor-to-sensor transformations of Landsat MSS to IRS LISS-I and acquisition date normal::zation with respect to a typical rice growth profile were also carried out. Using srch an empirical relation, rice yield was estimated for Kharif in 1988 using IRS-IA LISS-I data at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Yield models based on vegetation indices derived from spectral data have been developed for crops like rice (Ravi et at., 1992;Patel et al, 1991) and wheat Dnbey and Sharma, 1993). Development of yield models using SAR data is in the preliminary stage.…”
Section: Introductionmentioning
confidence: 95%
“…Yield models based on vegetation indices derived from spectral data have been developed for crops like rice (Ravi et at., 1992;Patel et al, 1991) and wheat Dnbey and Sharma, 1993). Development of yield models using SAR data is in the preliminary stage.…”
Section: Introductionmentioning
confidence: 95%
“…Rice has seen fewer studies (e.g. Patel et al, 1991;Tennakoon et al, 1992;Wang et al, 2010;Peng et al, 2014;Son et al, 2014) even though it is also a globally dominant agricultural commodity. Reasons for this are unknown but it could be a result of tending to be grown in more tropical, thus cloudy, regions make its monitoring from commonly used optical type sensors an increased challenge.…”
Section: Introductionmentioning
confidence: 98%
“…These images, in general, depict crop-specific characteristics, which could be important in developing pre-harvest yield forecasting models (Jing-Feng et al, 2002;Liu & Kogan, 2002;Prasad et al, 2006;Salazar et al, 2007;Mkhabela et al, 2011). For example: (i) Patel et al (1991) established an empirical relationship between the Indian Remote Sensing Linear Imaging Self Scanning (IRS LISS)-derived ratio between near infrared (NIR) and red (R) spectral bands and ground-based yield; and found that the coefficient of determination (R 2 ), root mean square error (RMSE), and deviations were 0.52, 2.62, and in the range 2-14%, respectively, over India; (ii) Rahman et al (2009;2012) utilized Advanced Very High Resolution Radiometer (AVHRR)-derived 7-day composite of normalized difference vegetation index (NDVI) and brightness temperature at 16 km resolution to compute several vegetation health-related indices such as vegetation condition index, temperature condition index, and vegetation health index in forecasting yield for two types of rice, i.e., aus and aman over Bangladesh. They observed that modelled and ground-based rice yield revealed a R 2 of 0.56 and 0.89 for aus and aman respectively; (iii) Savin & Isaev (2010) used MODIS-derived 10-day composite of NDVI at 250m resolution, fraction of absorbed radiation and two meteorological variables (i.e., temperature and incident solar radiation) to develop a process-based model for forecasting rice yield over Republic of Kalmykia.…”
Section: Introductionmentioning
confidence: 99%